Subarachnoid hemorrhage following posterior spinal artery aneurysm: A case report and review of the literature - S. Geibprasert (2018)
Isolated posterior spinal artery aneurysms are rare vascular lesions. We describe the case of a 43-year-old man presenting with spinal subarachnoid hemorrhage after a minor trauma who was found to have a dissecting aneurysm of a posterior spinal artery originating from the right T4 level. Endovascular treatment was not contemplated because of the small size of the feeding artery, whereas surgical resection was deemed more appropriate because of the posterolateral perimedullary location that was well appreciated on CT angiography. After surgical resection of the aneurysm the patient had a complete neurological recovery. In comparison to anterior spinal artery aneurysms whose pathogenesis is diverse, posterior spinal aneurysms are most often secondary to a dissection and represent false or spurious aneurysms. Although the definite diagnosis still requires spinal angiography, MRI and CT may better delineate the relationship of the aneurysm to the spinal cord in order to determine the best treatment method. Prompt treatment is recommended as they have high rebleeding and mortality rates.